High-resolution δ18O and δ13C records of an AMS 14C and 230Th/U dated stalagmite from Xinya Cave in Chongqing: Climate and vegetation change during the late Holocene. (15th August 2017) - Li, Jun-Yun; Li, Hong-Chun; Li, Ting-Yong; Mii, Horng-Sheng; Yu, Tsai-Lune; Shen, Chuan-Chou; Xu, Xiaomei
Abstract: Two stalagmites, XY07-8 and -11 collected from Xinya Cave in northeast Chongqing of China, were dated by 230 Th/U and AMS 14 C methods. The Holocene parts of the stalagmites contain high Th contents, resulting large uncertainties of the 230 Th/U ages. Two precise 230 Th/U dates in the pre-Holocene part of XY07-8 agree well with the AMS 14 C ages. The Holocene 14 C dates of the two stalagmites reveal a 600-year initial 14 C age which was probably introduced from the dissolved CO2 in the overlaying soil and transferred into the seepage water, supported by the AMS 14 C dating on soil organic carbon in an overlying soil profile near the cave. Based on the AMS 14 C and 230 Th/U dating results, a reliable chronology of the 22-cm part of XY07-8 has been established, revealing a continuous growth since 23 ka BP. The δ 18 O and δ 13 C records of the top 5.3-cm part of XY07-8 provide climate and vegetation changes over the past 4100 years. The comparisons of the XY07-8 δ 18 O record with the instrumental rainfall, historic dry-wet index and the stalagmite δ 18 O records from other caves in eastern China not only serve verification of the XY07-8 chronology, but also confirm the δ 18 O record as a monsoonal rainfall proxy. The XY07-8 δ 18 O record indicates that on millennial scale the intensity of East Asian Summer Monsoon was decreased from 4100 a BP to 2400 a BP following the decline of the summer insolation, then leveling out with decadal-to-centennial variations. On decadal-to-centennial scales, the XY07-8 δ 18 O record reveals wetness changes probably corresponding to variations in total solar irradiance (TSI), with lighter δ 18 O excursions reflecting wetter episodes under less TSI that is opposite to the δ 18 O – TSI correlation of the stalagmite records from the caves in north and south China. Furthermore, unlike the δ 18 O record, the δ 13 C record does not show the Holocene "insolation decline" trend, but generally following the decadal-to-centennial variations of the δ 18 O record and the TSI record except the last 150 years. Since 1850 CE, the XY07-8 δ 18 O has an enriched trend which reflects an arid trend in climate, but the δ 13 C has a depleted trend perhaps indicating human impacts on the vegetation and atmosphere CO2 . This study calls for the attention to the discrepancies and physical meanings of stalagmite δ 18 O on different time scales ("monsoon intensity" on millennium scale vs. "rainfall index" on decadal scale) and to the spatial disparity of monsoonal rainfall in eastern China.